Né surréaliste, trop surréaliste : Artaud au sein et en marge du mouvement - Swoboda, Tomasz (Romanica Silesiana)
The paper discusses some aspects of the conflict between Antonin Artaud and the surrealists, such as his personal relations with André Breton, ideological and political dissensions between them, as well as aesthetic and philosophical divergences. Breton’s and Artaud’s different attitudes towards revolution and madness disclose some crucial points in their literary works, and show up insuperable obstacles for their cooperation. Against this background, Artaud’s thought seems closer to Surrealism’s rebels and heretics, notably to Georges Bataille, rather than to Breton or Aragon with whom he worked for two years, all the same decisive period for his posterior writing. Key words: Antonin Artaud, André Breton, Surrealism, Madness, Revolution.